Data of cost-optimality and technical solutions for high energy performance buildings in warm climate - Ilaria Zacà; Delia D’Agostino; Paolo Maria Congedo; Cristina Baglivo (Data in Brief, 2015)
The data reported in this article refers to input and output information related to the research articles entitled Assessment of cost-optimality and technical solutions in high performance multi-residential buildings in the Mediterranean area by Zacà et al. (Assessment of cost-optimality and technical solutions in high performance multi-residential buildings in the Mediterranean area, in press.) and related to the research article Cost-optimal analysis and technical comparison between standard and high efficient mono residential buildings in a warm climate by Baglivo et al. (Energy, 2015, 10.1016/j.energy.2015.02.062, in press).